2006
DOI: 10.1017/s0967199405003503
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-induced hyperactivation-like vigorous flagellar movement in starfish sperm

Abstract: Asterosap, a sperm-activating peptide (SAP) from the starfish egg jelly coat, is diffusible and controls a cGMP-signalling pathway in starfish sperm in the same manner as resact, a potent chemoattracting SAP in sea urchins. This fact suggests that asterosap may serve as a chemoattractant like resact at concentrations with appropriate gradients. Since asterosap is one of three egg jelly components, which in concert induce the acrosome reaction, it is still worthwhile to evaluate how asterosap modulates sperm mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Sea urchin sperm swim straight in the presence of sperm-activating peptide (SAP) isoform P15 (Shiba et al, 2006). These reactions were almost similar among three Acropora species.…”
Section: Morita and Othersmentioning
confidence: 97%
“…Sea urchin sperm swim straight in the presence of sperm-activating peptide (SAP) isoform P15 (Shiba et al, 2006). These reactions were almost similar among three Acropora species.…”
Section: Morita and Othersmentioning
confidence: 97%
“…Shiba et al (2006) reported that starfish (Aphelasterias japonica) spermatozoa swam along circular paths with the head oscillating synchronously. Our studies on A. amurensis found that spermatozoa in ASW also swam along a circular path but beat frequency increased those in asterosap ( Fig.…”
Section: Asterosap Activate the Motility Of Spermatozoamentioning
confidence: 99%
“…Resact is a chemoattractant for sperm and it evokes elevations of intracellular Ca 2+ ([Ca 2+ ]i) in the flagellum (Garbers & Kopf, 1989;Kaupp et al, 2008). As in the case of sea urchin, in starfish, asterosap is also a chemotactic agent for sperm , Shiba et al, 2006. The increase in [Ca 2+ ]i elicits a turn in the sperm trajectory followed by a period of straight swimming called "turnand run" (Boehmer et al, 2005).…”
Section: Asterosap Is a Sperm-activating Moleculementioning
confidence: 99%